2020
DOI: 10.1002/cnr2.1284
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor γ is a therapeutically targetable driver of growth and survival in prostate cancer

Abstract: Background: Prostate cancer (PC) tissue contains all-trans retinoic acid (ATRA) at a very low level (10 −9 M), at least an order of magnitude lower than in adjacent normal healthy prostate cells or benign prostate hyperplasia. When this is coupled with deregulated expression of the intracellular lipid-binding proteins FABP5 and CRABP2 that is frequently found in PC, this is likely to result in the preferential delivery of ATRA to oncogenic PPARβ/δ rather than retinoic acid receptors (RARs). There are three iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…By contrast, when used at concentration of 5 nM (IC 50 ) (which is close to its K d value), treatment with the RARγ-selective antagonist AGN205728 led to growth arrest and cell death in cell lines (which was synergistic in combination with docetaxel). In agreement with the data from AGN194310, AGN205728 also inhibited the colony-forming potential of PCa [ 75 ] and breast cancer cell lines (unpublished data), again suggesting that both CSC-like and non-CSC-like cells were targeted. Confirming a survival-supportive role for RARγ within PCa cells, the RARγ-selective agonist AGN205327, and also 0.1 nM ATRA (a concentration that activates only the RARγ isotype), both increased PCa colony formation.…”
Section: Antagonising Rarγ Kills Cancer Stem Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…By contrast, when used at concentration of 5 nM (IC 50 ) (which is close to its K d value), treatment with the RARγ-selective antagonist AGN205728 led to growth arrest and cell death in cell lines (which was synergistic in combination with docetaxel). In agreement with the data from AGN194310, AGN205728 also inhibited the colony-forming potential of PCa [ 75 ] and breast cancer cell lines (unpublished data), again suggesting that both CSC-like and non-CSC-like cells were targeted. Confirming a survival-supportive role for RARγ within PCa cells, the RARγ-selective agonist AGN205327, and also 0.1 nM ATRA (a concentration that activates only the RARγ isotype), both increased PCa colony formation.…”
Section: Antagonising Rarγ Kills Cancer Stem Cellssupporting
confidence: 88%
“…Cell death provoked by the RAR pan-antagonist AGN194310 and the RARγ-selective antagonist AGN205728 was found to be mitochondria-dependent and caspase-independent [ 74 , 75 ]. This process, seen also for retinoid-deprived Jurkat T-cell leukemia cells, is termed necroptosis and it occurs via poly-(ADP-ribose) polymerase PARP-1 activation [ 77 ].…”
Section: The Oncogenic Action Of Rarγmentioning
confidence: 99%
“…Future studies are needed to investigate whether treatment with the combination of RAR antagonists and osimertinib promotes the regression of advanced brain metastatic lesions in EGFR-mutant lung cancer patients. Of relevance, multiple high-affinity RAR antagonists were developed in the late 1990s (55) and are currently the subject of renewed interest for their ability to inhibit prostate cancer growth (56,57). With the increasing prevalence of brain metastasis in EGFR-mutant lung cancer patients and its associated poor prognosis (39), therapeutic strategies that can prevent or treat brain relapses in these patients will be of high translational relevance and direct clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…We found that administration of Palo or ATRA decreased the tumor volumes, raising the issues of whether this is due to a direct effect of Palo or ATRA on tumor cells or an indirect effect through inhibition of tumor-induced bone. Published data suggest that RAR agonists are not very effective in inducing growth arrest in PCa cell lines in vitro, as high concentrations (~1– 10 μM) are generally needed (5052), instead RAR antagonists are more effective in inhibiting PCa cell proliferation in vitro (5355). We also found that Palo or ATRA did not significantly inhibit proliferation of C4-2b-BMP4, TRAMP-BMP4, and MycCaP-BMP4 cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%